EFFECT OF LEARNING APPROACH ON STUDENT LEARNING OUTCOMES - Turdjai, Turdjai (UNIB Press, 2016)
Abstract: The purpose of this study to determine the effect of differences in the individual learning and group learning approach toward learning outcomes on student of Post-garduate Program of Education Technology, Faculty of Teacher Training and Education University of Bengkulu. The method used in this study is a randomized quasi- experimental with two matched group pretest - posttest design. The research instrument is a test, with data analysis techniques were descriptive statistical analysis and the